Drop-Weight Impact Tests on Engineered Cementitious Composites heated to 500 oC - Raad A. Al-Ameri; Mustafa Özakça; Esra Eylem Karataş; M Tolga Göğüş; A. Hamza Tanrıkulu (Wasit Journal of Engineering Sciences)
Despite that concrete is a fire-resisting construction material, its microstructure suffers significant chemical and physical changes when subjected to temperatures higher than 400 oC. Therefore, the combined effect of unexpected impacts and fire can lead to the collapse of the structure. To evaluate this combined effect, an experimental program was directed in this study using the ACI 544-2R repeated impact test method. Shallow cylindrical specimens with 150 mm diameter and 64 mm depth were prepared to evaluate the cracking and failure impact strengths of normal strength concrete (NC) and engineered cementitious composites (ECC). The ECC mixture was reinforced with 2% of polypropylene fibers. In addition to the impact strength, the compressive and flexural strengths of NC and ECC mixtures were also investigated. The impact, compressive and flexural tests were performed on unheated specimens and others heated to 500 oC to evaluate the residual strengths of NC and ECC mixtures. The results showed that before heating, ECC exhibited a failure impact performance that is approximately 6 times more ductile than that of NC, where the retained failure impact numbers of NC and ECC were 57 and 259 blows, respectively. However, both mixtures lost approximately 95% of their impact strengths after exposure to 500 oC.